Thermal Performance, Indoor Air Quality, and Carbon Footprint Assessment in Airport Terminal Buildings - Mehmet Kadri Akyüz; Emin Açıkkalp; Önder Altuntaş (Buildings)
This study explores energy consumption, thermal performance, and indoor environmental quality (IEQ) in terminal buildings. Through detailed thermal analysis, this research identifies key sources of heat loss, such as thermal bridges in walls and windows, which significantly increase energy demands for heating. IEQ measurements show that the lack of mechanical ventilation, combined with high passenger densities, frequently leads to CO2 levels exceeding recommended thresholds, highlighting the urgent need for improved ventilation systems. Energy requirements were calculated based on the TS 825 standard and compared to actual consumption data, showing that optimizing boiler settings could save 22% of heating energy without any additional investment. Simulations and economic analyses further showed that adding thermal insulation to the building envelope and installing double-glazed windows with improved U-values could achieve significant energy savings and reduce CO2 emissions, all with favorable payback periods. A life cycle assessment (LCA) was conducted to evaluate the environmental impact of these interventions, demonstrating significant reductions in the airport’s carbon footprint. The findings underscore the importance of aligning operational standards with international guidelines, such as ASHRAE and CIBSE, to ensure thermal comfort and optimize energy use.